The Role and Mechanisms of Traditional Chinese Medicine for Airway Inflammation and Remodeling in Asthma: Overview and Progress - Zhou, Bo-wen; Liu, Hua-man; Jia, Xin-hua (Frontiers in Pharmacology, 2022)
Asthma as an individual disease has blighted human health for thousands of years and is still a vital global health challenge at present. Though getting much progress in the utilization of antibiotics, mucolytics and especially the combination of inhaled corticosteroids (ICS) and long acting β-agonists (LABA), we are confused of the management of asthmatic airway inflammation and remodeling which directly threatens the quality of life for chronic patients. The blindly addition of ICS will not benefit the remission of cough, wheeze or sputum, but to increase the risk of side effects. Thus, it is necessary to explore an effective therapy to modulate asthmatic inflammation and airway remodeling. Traditional Chinese Medicine (TCM) has been justified its anti-asthma effect in clinical practice but its underlying mechanism and specific role in asthma are still unknown. Some animal studies demonstrated that the classic formula, direct exacts and bioactive compounds isolated from TCM could significantly alleviate airway structural alterations and exhibit anti-inflammatory effect. By investigating these findings and data, we will discuss the possible pathomechanism underlined airway inflammation and remodeling in asthma, and the unique role of TCM in the treatment of asthma through regulating different signaling pathways.